Global, regional, and national trends and burden of diabetes mellitus type 2 among youth from 1990 to 2021: an analysis from the global burden of disease study 2021 - Deng, Ling; Lu, Shuihua; Zeng, Jianfeng; Liu, Houming (Frontiers in Endocrinology, 2025)
BackgroundAlthough studies have looked at type 2 diabetes mellitus (T2DM) in adults, global studies on youth with T2DM are relatively scarce. Understanding the global, regional, and national trends and burden of T2DM in this special population is critical to developing effective preventive control measures and strategies. Therefore, this study aims to shed light on the specific challenges facing different populations and regions to ultimately guide global action.MethodsBased on the Global Burden of Diseases, Injuries, and Risk Factors Study 2021, the incidence, prevalence, and Disability-Adjusted Life Years (DALYs) of youth with T2DM aged 15–24 years from 1990 to 2021 were extracted and analyzed at global, regional, and national levels. Point estimates with 95% uncertainty intervals (UIs) were used to calculate the average annual percentage changes (AAPCs) of incidence, prevalence, and DALYs. Subsequently, trends were thoroughly analyzed at the global, regional, and national levels, and the global trends were analyzed in detail by factors like age, sex, and social development index.ResultsThe global incidence, prevalence, and DALYs of T2DM in youth increased to varying degrees from 1990 to 2021. With an AAPC of 2.62 (95% CI: 2.42 - 2.81), the global incidence of T2DM increased from 56.0 per 100–000 population in 1990 to 123.9 per 100–000 population in 2021. The incidence of increase in males (AAPC 2.68, 95% CI: 2.47 - 2.89) was higher than in females (AAPC 2.51, 95% CI: 2.35 - 2.66). The incidence increased with increasing age, but the largest increase was found in youth aged 15–19 years (AAPC 2.72, 95% CI: 2.47 - 2.96). High SDI areas saw the greatest increase in incident rates (AAPC 3.48, 95% UI: 3.43 - 3.52) compared with other areas.ConclusionThe increasing global incidence, prevalence, and DALYs of T2DM in youth presented a large burden to public health over the past thirty years, while the trends and burden vary by region, nation, gender, age, and level of development. Our study highlights the significance of developing targeted public health policies and strategies to respond to the heterogeneity among youth with T2DM.